Dinamika Almanak Masa Pra Islam Hingga Era Islam; Studi atas Penanggalan Sistem Solar, Lunar dan Luni-Solar - Nihayatur Rohmah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2019)
Calendar is an expression of the rhythm of collective activity and at the same time serves to ensure its order. Therefore, various civilizations from ancient times to the present give serious attention to arranging their calendar systems in accordance with the philosophy, outlook on life and traditions of the civilization. Determining the almanac is a reality produced by a handful of elites (read: important groups of people in power in society) who are full of interests. The Arabs used to apply the almanac based on the solar system (Sun), then switch to the lunar system (Moon). The pre-Islamic Arabs had the habit of counting the months with the appearance of the new moon, but irregularly added once a month in three years to harmonize the date with the seasons, so that it was not purely applying the lunar calendar but rather the luni-solar system. This intercalarymonth was then used by pre-Islamic Arabs as a tool to play the month of Muharram which was forbidden to carry out warfare. Qs. At-Taubat: 36 confirms the prohibition of the practice of intercalation (an-nasi ') and the commencement of a lunar-based calendar system. So that since Muhammad's apostolate until now the calendar system has been organized, namely to make the Moon the basis of its stipulation.The shift, change and even improvement of the dating system as part of the dynamics of the dating of the Arabs during the pre-Islamic era to the Islamic era